American Covenant a History of Civil Religion from the Puritans to the Present - Gorski, Philip S. 1963- (Princeton University Press, 2017)
The long battle between exclusionary and inclusive versions of the American storyWas America founded as a Christian nation or a secular democracy? Neither, argues Philip Gorski in American Covenant. What the founders envisioned was a prophetic republic that would weave together the ethical vision of the Hebrew prophets and the Western political heritage of civic republicanism. In this eye-opening book, Gorski shows why this civil religious tradition is now in peril—and with it the American experiment.American Covenant traces the history of prophetic republicanism from the Puritan era to today, providing insightful portraits of figures ranging from John Winthrop and W.E.B. Du Bois to Jerry Falwell, Ronald Reagan, and Barack Obama. Featuring a new preface by the author, this incisive book demonstrates how half a century of culture war has drowned out the quieter voices of the vital center, and demonstrates that if we are to rebuild that center, we must recover the civil religious tradition on which the republic was founded
Description based on online resource; title from PDF title page (publisher's Web site, viewed 20. Jun 2019)
Keywords: Geschichte 1850-2017; HISTORY / United States / General; Zivilreligion; USA